2018
DOI: 10.1111/trf.14988
|View full text |Cite
|
Sign up to set email alerts
|

Higher intraoperative plasma transfusion volumes are associated with inferior perioperative outcomes

Abstract: Background: Intraoperative plasma transfusion is common, yet little is known regarding its effects on perioperative coagulation tests or clinical outcomes. Study Design and Methods: This is a retrospective cohort study of adults receiving intraoperative plasma transfusion at a single center from 2011–2015. Relationships between plasma transfusion volume, changes in coagulation test values, and clinical outcomes, including a primary outcome of early postoperative RBC transfusion, were assessed with multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Some studies focused on cardiac surgery indicated that a high FFP-to-RBC ratio in MT can improve survival ( 18 , 19 , 29 ). In contrast, according to the observation in a large tertiary hospital, a greater intraoperative plasma transfusion volume was associated with fewer hospital-free days in heterogenous surgeries with or without MT ( 17 , 30 , 31 ). Multicenter cohort studies also suggested a significant association between FFP transfusion and increased mortality in patients with gastrointestinal bleeding ( 32 34 ).…”
Section: Discussionmentioning
confidence: 95%
“…Some studies focused on cardiac surgery indicated that a high FFP-to-RBC ratio in MT can improve survival ( 18 , 19 , 29 ). In contrast, according to the observation in a large tertiary hospital, a greater intraoperative plasma transfusion volume was associated with fewer hospital-free days in heterogenous surgeries with or without MT ( 17 , 30 , 31 ). Multicenter cohort studies also suggested a significant association between FFP transfusion and increased mortality in patients with gastrointestinal bleeding ( 32 34 ).…”
Section: Discussionmentioning
confidence: 95%